Campus emergency notification systems: Lessons learned from a miscommunication. Issue 9 (19th December 2018) - Patten, Ryan; Ruddell, Rick; Thomas, Matthew O.
Abstract : The ability to instantly notify tens of thousands of students and campus personnel about potential or actual threats at an institution of higher education has become an important crisis communications tool for campus security and police departments. Used correctly, these emergency notification systems can reduce threats to life and property. The most common uses of emergency notification systems are for severe weather communication, law enforcement emergencies, class cancellations, and traffic or construction updates.